2011
DOI: 10.3109/02770903.2011.578315
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Rate of Exercise-Induced Bronchoconstriction in Annaba (Algeria) Schoolchildren

Abstract: These features of a fairly high bronchial hyperresponsiveness could be facilitated by the polluted environment of the city.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…De Baets et al 7 found an EIB prevalence of 8.5% in girls and 6.4% in boys, while Busquets et al 9 also reported a higher prevalence of EIB among girls (13%) than boys (9%). In contrast, other studies did not reveal any gender differences 10 20…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…De Baets et al 7 found an EIB prevalence of 8.5% in girls and 6.4% in boys, while Busquets et al 9 also reported a higher prevalence of EIB among girls (13%) than boys (9%). In contrast, other studies did not reveal any gender differences 10 20…”
Section: Discussionmentioning
confidence: 63%
“…The prevalence of EIB among 10–12-year-old children in Algeria was 16.1% when the 6 min free-running test was used and EIB was defined as a decrease of ≥15% in peak expiratory flow rate 10. Using the same exercise protocol for investigating 13–14-year-old adolescents, Busquets et al 9 found a prevalence of 11%, while De Baets et al 7 found a prevalence of 7.4% among primary school children.…”
Section: Discussionmentioning
confidence: 99%
“…The first visit consisted of an interview about asthma, medication, measurements of height, weight, fractional exhaled nitric oxide (FeNO) and venous blood samples for analyses of Immunoglobulin E (IgE) sensitization and eosinophil cationic protein (ECP). The second visit (at an average of 12 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) days later (median (interquartile range)) consisted of a standardized exercise challenge test on a treadmill with dry-air inhalation to detect EIB. 5 Ethical approval was obtained from the ethics review board in Uppsala, Sweden (Dnr 2011/413).…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6] Some studies have reported a higher prevalence in girls than in boys, 7,8 while others have not revealed any gender differences. 9,10 Exercise test is recommended to confirm EIB as exercise-induced symptoms have poor predictive value for EIB. 7,11,12 Guidelines from the European Respiratory Society (ERS) 13 and the American Thoracic Society (ATS) 14 and the recent EIB clinical practice guideline from the ATS recommend laboratory exercise testing, that is, a standardized exercise-challenge test.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a recent study conducted in the city of Annaba on 286 (asthmatic and non-asthmatic) schoolchildren aged 10-12 years has demonstrated that the characteristics of a high bronchial hyperresponsiveness could be facilitated by the polluted environment of the city (Benarab-Boucherit et al, 2011). Furthermore, in the clinical-biological study published by Boumendjel in 2012, exposure to airborne allergens was approached via the data of a questionnaire, without the visit and exploration of the patient's home environment.…”
Section: Introductionmentioning
confidence: 99%